The under reporting of women’s economic activity in Bangladesh: An examination of official statistics - Mahmud, Simeen; Tasneem, Sakiba (BRAC Development Institute (BDI), 2022)
In Bangladesh, women are engaged in a variety of economic activities ranging from homestead based expenditure saving activities to outside paid work. However, women’s work always remains under-reported, especially women’s non‐market homestead based economic activities. Underreporting is particularly critical in the case of official statistics. The types of work women are involved in are often overlooked by women themselves. Non-recognition of women’s economic activity not only leads to the undervaluation of women’s economic contribution but also contributes to their lower status in society relative to men. This paper intended to explore why official statistics fail to enumerate the entirety of women’s economic activity in Bangladesh. To do this, we used different definitions of economic activity (work) used by the Bangladesh Bureau of Statistics (BBS) to estimate women’s LFPR for women aged 15 and above in 69 villages of eight districts of Bangladesh. The study finds that the female LFPR ranges between 4% and 16 % in the eight districts when economic activity is defined in the narrowest sense, i.e. outside paid work in the last 12 months. These rates become considerably higher (increases by 3‐16 folds) if market work inside the home is taken into account along with the paid work. If we further extend our definition to include women’s expenditure saving activities in the last 12 months, the rates rise further ranging from 55% to 82% in the eight districts. The paper argues that widely held beliefs regarding women’s work contribute to the under-reporting of women’s economic activity by official statistics, in addition to data collection constraints in the field like inadequate time and work burden of investigators.